The Effectiveness of Digital Content Marketing Strategy, Community Participation, and Tourist Satisfaction on Promotion Improvement in Bahbolon Hutabayu Tourism Village - Sabrina Zahwa; Budi Prayogi; Fizra Kartika; Oky Ratna Zega (The Postgraduate School of Tourism Sahid Polytechnic, 2026)
This study aims to analyze the effect of digital content marketing, community participation, and tourist satisfaction on promoting Bahbolon Hutabayu Tourism Village. The background of this study stems from the weak promotion of tourism villages despite their great natural and cultural potential. This study uses a quantitative approach by distributing questionnaires to 50 tourist respondents. The data were analyzed using validity and reliability tests, classical assumption tests, and multiple linear regression using SPSS 22 software. The results show that, partially, digital content marketing (X1) and tourist satisfaction (X3) have a significant effect on promotion improvement (Y), while community participation (X2) has no significant effect. Simultaneously, the three variables significantly affect promotion improvement with an Adjusted R² value of 0.600, which means that 60% of the variation in promotion improvement can be explained by variables X1, X2, and X3. These findings confirm that digital promotion strategies and tourist experiences are key factors in strengthening destination promotion, while increased community participation is still needed to support the sustainability of promotion. This study implies that tourism village managers need to strengthen digital content, improve service quality, and empower the community to create more effective and sustainable promotion.